Protective role of acetylsalicylic acid in experimental Trypanosoma cruzi infection: evidence of a 15-epi-lipoxin A₄-mediated effect. - Alfredo Molina-Berríos; Carolina Campos-Estrada; Natalia Henriquez; Mario Faúndez; Gloria Torres; Christian Castillo; Sebastián Escanilla; Ulrike Kemmerling; Antonio Morello; Rodrigo A López-Muñoz; Juan D Maya (Public Library of Science (PLoS), 2013)
Chagas' disease, produced by Trypanosoma cruzi, affects more than 8 million people, producing approximately 10,000 deaths each year in Latin America. Migration of people from endemic regions to developed countries has expanded the risk of infection, transforming this disease into a globally emerging problem. PGE₂ and other eicosanoids contribute to cardiac functional deficits after infection with T. cruzi. Thus, the inhibition of host cyclooxygenase (COX) enzyme emerges as a potential therapeutic target. In vivo studies about the effect of acetylsalicylic acid (ASA) upon T. cruzi infection are controversial, and always report the effect of ASA at a single dose. Therefore, we aimed to analyze the effect of ASA at different doses in an in vivo model of infection and correlate it with the production of arachidonic acid metabolites. ASA decreased mortality, parasitemia, and heart damage in T. cruzi (Dm28c) infected mice, at the low doses of 25 and 50 mg/Kg. However, this effect disappeared when the high ASA doses of 75 and 100 mg/Kg were used. We explored whether this observation was related to the metabolic shift toward the production of 5-lipoxygenase derivatives, and although we did not observe an increase in LTB4 production in infected RAW cells and mice infected, we did find an increase in 15-epi-LXA₄ (an ASA-triggered lipoxin). We also found high levels of 15-epi-LXA₄ in T. cruzi infected mice treated with the low doses of ASA, while the high ASA doses decreased 15-epi-LXA₄ levels. Importantly, 15-epi-LXA₄ prevented parasitemia, mortality, and cardiac changes in vivo and restored the protective role in the treatment with a high dose of ASA. This is the first report showing the production of ASA-triggered lipoxins in T. cruzi infected mice, which demonstrates the role of this lipid as an anti-inflammatory molecule in the acute phase of the disease.